2021
DOI: 10.3389/fncir.2021.657445
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic Modulation of Persistent Inward Currents in Serotonergic Neurons of Medulla in ePet-EYFP Mice

Abstract: Serotonergic (5-HT) neurons in the medulla play multiple functional roles associated with many symptoms and motor activities. The descending serotonergic pathway from medulla is essential for initiating locomotion. However, the ionic properties of 5-HT neurons in the medulla remain unclear. Using whole-cell patch-clamp technique, we studied the biophysical and modulatory properties of persistent inward currents (PICs) in 5-HT neurons of medulla in ePet-EYFP transgenic mice (P3–P6). PICs were recorded by a fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…We classified these patterns into three types based on differences in onset and offset voltages of PICs. In fact, six patterns of PICs have been described previously in locomotor‐activated spinal interneurons (Dai & Jordan, 2010) and four patterns in the brainstem serotonergic neurons (Cheng et al., 2021; Ge & Dai, 2020). PICs have been shown to be responsible for variable patterns of repetitive firing induced by current bi‐ramps (Harvey et al., 2006; Lee & Heckman, 1998, 2001; Powers & Binder, 2003; Powers et al., 2008).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We classified these patterns into three types based on differences in onset and offset voltages of PICs. In fact, six patterns of PICs have been described previously in locomotor‐activated spinal interneurons (Dai & Jordan, 2010) and four patterns in the brainstem serotonergic neurons (Cheng et al., 2021; Ge & Dai, 2020). PICs have been shown to be responsible for variable patterns of repetitive firing induced by current bi‐ramps (Harvey et al., 2006; Lee & Heckman, 1998, 2001; Powers & Binder, 2003; Powers et al., 2008).…”
Section: Discussionmentioning
confidence: 94%
“…Incomplete space clamp is a problem for almost all studies using whole cell patch‐clamp techniques (Cheng et al., 2021; Dai & Jordan, 2011). Any voltage‐dependent current could be contaminated by the unclamped currents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuronal excitability is generally characterized not only by voltage threshold, but also by recruitment (I rec ) and decruitment (I dec ) currents (e.g., Cheng et al, 2020 ; Cheng et al, 2021 ). In the present study, we defined the recruitment current as the current ramp at which the first spike was initiated ( Figures 3A1,A2 , red dots) and decruitment current as the current ramp at which the last spike was elicited ( Figures 3B1,B2 ).…”
Section: Resultsmentioning
confidence: 99%
“… 15 , 16 Previous studies have reported that persistent sodium channels regulate Vth and repetitive firing in spinal motoneurons, 36 interneurons, 76 hippocampal neurons, 77 and brainstem 5-HT neurons. 78 In addition, persistent sodium channels are critical in regulating pacemakers and locomotion speed. 79 Recent studies have discovered that 3 weeks of treadmill training increases neuronal excitability through the enhancement of persistent sodium channels in spinal interneurons 15 and midbrain 5-HT neurons in mice.…”
Section: Exercise Modulates Ion Channelsmentioning
confidence: 99%